Pelatihan dan Penyuluhan UKS Pintar Berbasis Homescholing Terhadap Guru MI Miftahul Mubtadin Pakong Sebagai Upaya Mencetak Generasi Sehat dan Pencegahan Covid-19 - Mohammad Imam Sufiyanto; Fatimatuz Zahra; Mohammad Fausi (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
UKS (School Health Unit) is one of the health business units in schools that is interesting to implement, because it has efforts to prevent disease in a curative way, the benefits will not be obtained in the near future, but will be felt in the long term. These characteristics make UKS efforts need to be encouraged for health and disease prevention by the community which are deemed difficult to be carried out continuously. The purpose of this activity is to provide counseling and training in health management in Pakong, and prevention of disease and health. This research is a qualitative research with a descriptive approach. Sources of data in this study are primary data and secondary data. Meanwhile, the data collection procedure used three ways, namely interviews, observation and documentation. While the analysis used is deductive and inductive. The result of this activity is to train teachers to be skilled in disease prevention and handling of health in schools and infectious diseases.